2013
DOI: 10.2478/s11756-013-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and assessment of genetic stability in Celastrus paniculatus: An endangered medicinal plant

Abstract: A highly efficient protocol for in vitro regeneration of an indigenous, endangered medicinal plant Celastrus paniculatus was achieved using nodal explants. Murashige and Skoog (MS) basal medium supplemented with 0.5 mg/L 6-benzylaminopurine (BAP) and 0.1 mg/L naphthaleneacetic acid (NAA) showed maximum percentage of shoot multiplication (83.4%) with 8.2 shoots/explants. Maximum rooting of 73.3% with 4.8 roots/shoot was achieved on half-strength MS media supplemented with 0.5 mg/L indole-3-acetic acid (IAA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The overall banding profile obtained from total of 2,350 bands (number of plants analysed 9 total number of scorable bands from RAPD and ISSR primers) were generated from the mother plant and 24 in vitro raised clones. All banding profiles were monomorphic in nature, similar to those of the mother plants indicating homogeneity among the regenerated culture and genetic uniformity with that of the donor plants similar to results of Senapati et al (2013), Saha et al (2014). This is the first report of genetically sustainable micropropagation protocol of O. canum from nodal explants.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The overall banding profile obtained from total of 2,350 bands (number of plants analysed 9 total number of scorable bands from RAPD and ISSR primers) were generated from the mother plant and 24 in vitro raised clones. All banding profiles were monomorphic in nature, similar to those of the mother plants indicating homogeneity among the regenerated culture and genetic uniformity with that of the donor plants similar to results of Senapati et al (2013), Saha et al (2014). This is the first report of genetically sustainable micropropagation protocol of O. canum from nodal explants.…”
Section: Resultsmentioning
confidence: 50%
“…A better analysis of genetic stability of plantlets can be made by using a combination of two types of markers, which amplify (Martins et al 2004). Genetic integrity by RAPD and ISSR analysis has been reported earlier in many medicinal plant species (Senapati et al 2013;Saha et al 2014). Out of a total of 30 RAPD and 17 ISSR primers, 17 RAPD and nine ISSR primers were selected based on their reproducibility (Tables 6, 7).…”
Section: Resultsmentioning
confidence: 98%
“…Lal and Singh (2010) found the maximum number of shoots (8.9 ± 0.5) along with hundred per cent bud break in the MS medium supplemented with 1.0 mgl-1 BAP. Senapati et al (2013) observed that the Murashige and Skoog (MS) basal medium supplemented with 0.5 mg/L 6-benzylaminopurine (BAP) and 0.1 mg/L naphthalene acetic acid (NAA) showed maximum percentage of shoot multiplication (83.4%) with 8.2 shoots/explants.…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…Lal and Singh (2010) proved that the MS half strength medium supplemented with 0.5 mgl-1 NAA best with hundred per cent rooting. Senapati et al, (2013) was achieved Maximum rooting of 73.3% with 4.8 roots/shoot on halfstrength MS media supplemented with 0.5 mg/L indole-3-acetic acid (IAA) and the percentage of survival was 91% after acclimatization.…”
Section: In Vitro Rootingmentioning
confidence: 99%
“…None of the members is listed in the Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES). In vitro multiplication of threatened members like C. paniculatus has been reported by using different explants (Nair and Seeni 2001 ;De Silva and Senarath 2009 ;Senapati et al 2013 ). Information on regeneration of other threatened important members such as H. africana and C. scandens is not available yet.…”
Section: Threats and Conservationmentioning
confidence: 99%